PERAN POLITEKNIK MENGEMBANGKAN UMKM DALAM PERSAINGAN GLOBAL - Prayitno Prayitno; Hesti Widianti; Tabrani Tabrani (Monex: Journal of Accounting Research, 2019)
The trend of globalization followed by uncontrolled technological changes has resulted in the growth of businesses that are increasingly changing, those changes must automatically be followed by local actors but the local actors who initially because by accident are unable to compete with large-scale business sectors that start their business by design, experience micro small and Medium Enterprises is good but not supported by good formal knowledge so the results will be inferior to those designed so that the role of polytechnics is needed to provide applicative solutions needed by the micro small and Medium Enterprises actors, polytechnics need an applicable solution because polytechnic education concepts are more practiced than academic. The polytechnic has the role of providing theory and practice in management, accounting, marketing, relationships with banks, networks and practical solutions so that SMEs are able to compete with large companies. Keywords: globalization, vocational education, applicable